Transformasi Keselamatan Dan Kesehatan Kerja: Menciptakan Lingkungan Kerja Yang Mendorong Kreativitas dan Inovasi di Indonesia - Studi Literatur - Ramadhani, Nur Fitri; Yuliana, Yuliana; Dhafyah, Athaya Aqilah; Pabuntang, Tika (Annusfy : Journal of Multidisciplinary Research, 2025)
This study analyzes the transformation of K3 in Indonesia from an administrative obligation to a strategic element to support a creative work environment. Through a systematic review (PRISMA 2020) of 15 out of 450 articles, this study revealed three key findings: (1) K3 creates psychological safety as a psychological foundation; (2) K3 increases motivation and job satisfaction; and (3) K3 encourages organizational innovation through employee participation. In conclusion, K3 is a strategic investment for organizational competitiveness that needs to be integrated into HR strategies. Recommendations for further research are longitudinal empirical studies.